2015
DOI: 10.4103/1463-1741.165057
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure and cognitive performance: A study on personnel on board Royal Norwegian Navy vessels

Abstract: Prior research shows that work on board vessels of the Royal Norwegian Navy (RNoN) is associated with noise exposure levels above recommended standards. Further, noise exposure has been found to impair cognitive performance in environmental, occupational, and experimental settings, although prior research in naval and maritime settings is sparse. The aim of this study was to evaluate cognitive performance after exposure to noise among personnel working on board vessels in the RNoN. Altogether 87 Navy personnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 22 publications
4
43
0
1
Order By: Relevance
“…Here, we examined the performance on a well-known and widely utilized cognitive inhibition task among a homogeneous group of gamers of the FPS game CS:GO and compared their performance to a non-gaming sample. The apparent importance of cognitive inhibition for CS:GO and first-person shooter games in general may be tied to the importance of this cognitive skill for military personnel (Irgens-Hansen et al, 2015;Makhani et al, 2015). The scenario where distinguishing between friend and foe and deciding quickly and accurately whether to engage a target occurs regularly during CS:GO matches and often has a significant consequence to the outcome of a match.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we examined the performance on a well-known and widely utilized cognitive inhibition task among a homogeneous group of gamers of the FPS game CS:GO and compared their performance to a non-gaming sample. The apparent importance of cognitive inhibition for CS:GO and first-person shooter games in general may be tied to the importance of this cognitive skill for military personnel (Irgens-Hansen et al, 2015;Makhani et al, 2015). The scenario where distinguishing between friend and foe and deciding quickly and accurately whether to engage a target occurs regularly during CS:GO matches and often has a significant consequence to the outcome of a match.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of music on performance remains controversial, with some studies reporting a beneficial effect on performance in the OR, 12,14,[16][17][18] whereas others have found that music is harmful to the surgeons' focus, which could increase complication rates. 2,3,[5][6][7]15 The benefits or adverse effects of music within our OR was not assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…10,23 In human medicine, loud OR have been associated with increased stress levels of OR staff, which can affect performance and concentration and thereby increase the risk of surgical complications. 2,[5][6][7]15,24 A study by Engelmann et al 15 identified a correlation between endogenous cortisol levels of surgeons during surgical procedures and noise levels in the OR by comparing these levels before and after a noise reduction program was instituted. Elevations in OR noise during surgery has also been found to correlate with the incidence of surgical site infections in man.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations